2013
DOI: 10.1088/0268-1242/28/11/115010
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of temperature instability in InGaZnO thin-film transistors by in situ nitrogen doping

Abstract: We have investigated the effect of nitrogen doping on the behavior of hysteresis curve and its suppression of temperature instability in amorphous InGaZnO thin-film transistors (a-IGZO TFTs). The in situ nitrogen doping reduced the temperature induced abnormal sub threshold leakage current and traps generation. Large falling-rate (F R ) ∼ 0.26 eV V −1 , low activation energy (E a ) ∼ 0.617 eV and a small hysteresis compared to the pure a-IGZO TFTs, shows the best immunity to thermal instability. This is mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…[ 47 ] More recently, Zhao et al [ 48 ] and Chen et al [ 49 ] reported on highly-effi cient fl exible inverted polymer solar cells, achieving PCEs >8% with PFN as the ETL and by exploiting microcavity and plasmonic effects, respectively. [ 7,18,21,22,37 ] Our protocol includes an ammonia-treatment of the aqueous AZO nanoparticle solution (s-AZO) to produce more compact, crystalline, and smooth buffer layers that retain Al doping while incorporating N in small amounts (<1 at%), [52][53][54] leading to improved passivation of the dangling bonds. [ 50 ] In this contribution, we report on the facile and lowtemperature (125 °C) solution-processed deposition of AZO buffer layers-an effective approach in the making of electron transporting/hole blocking buffer layers for a wide range of polymer:PCBM BHJ systems-and demonstrate maximum PCEs of over 10% on glass and over 8% on plastic substrates without the requirement for ETL surface modifi cation/passivation.…”
mentioning
confidence: 99%
“…[ 47 ] More recently, Zhao et al [ 48 ] and Chen et al [ 49 ] reported on highly-effi cient fl exible inverted polymer solar cells, achieving PCEs >8% with PFN as the ETL and by exploiting microcavity and plasmonic effects, respectively. [ 7,18,21,22,37 ] Our protocol includes an ammonia-treatment of the aqueous AZO nanoparticle solution (s-AZO) to produce more compact, crystalline, and smooth buffer layers that retain Al doping while incorporating N in small amounts (<1 at%), [52][53][54] leading to improved passivation of the dangling bonds. [ 50 ] In this contribution, we report on the facile and lowtemperature (125 °C) solution-processed deposition of AZO buffer layers-an effective approach in the making of electron transporting/hole blocking buffer layers for a wide range of polymer:PCBM BHJ systems-and demonstrate maximum PCEs of over 10% on glass and over 8% on plastic substrates without the requirement for ETL surface modifi cation/passivation.…”
mentioning
confidence: 99%
“…We reported that larger concentration variation of V O in AOS TFTs could lead to serious V TH shift during the thermal testing [29]. In addition, the literature [16,34] indicated that N-doping suppressed V O formation in the bulk channels for the thermal tests of a-IGZO:N TFTs. Hence, the better thermal stability of Sample II might be attributed to the a-IGZO:N films, which acted as a passivation layer and suppressed the V O formation in the a-IZO:N layers.…”
Section: Resultsmentioning
confidence: 90%
“…Interstitial hydrogen (H i ) is also predicted to act exclusively as a donor, i.e., always in the 1þ charge state. 27 These induced Ho and H i defects are denoted by the purple bar and dashed curve in Fig. 1(b) and related to the large negative shift of V TH and V 0 observed in the a-IGZO TFT with "H:100 s." N is often considered as a promising p-type dopant and to serve as defect binder (i.e., facile substitution) due to its ionic radius close to that of O defects related to Vo.…”
Section: Ssmentioning
confidence: 99%
“…These observations imply that traps can be neutralized by a proper amount of H/N co-doping. It is indeed well known that the V TH and SS of the TFTs are related to the interface trap density (D it ) and the number of deep states, such that SS can be described as 27…”
mentioning
confidence: 99%